Cultural Memory As a Line of Defense In Preserving Cirebon's Multicultural Identity (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
This study examines the role of material culture in preserving the multicultural identity of the Cirebonese through the lens of cultural materialism, emphasizing the influence of physical infrastructure on cultural values and how material culture objects are internalized into cultural memory to sustain a shared identity. Using qualitative methods, data collection involves observation, interviews, and documentation to identify objects representing multicultural values. The findings reveal that Cirebon's culture stems from its historical ethnic diversity, influenced by its geographical location as a coastal trade hub since the 14th century. The establishment of an Islamic kingdom in the 15th century further shaped society, merging pre-existing Hindu cultural elements with Islamic traditions and those of Chinese and Arab traders. Material culture, including architecture, places of worship, and art, reflects and reinforces this multicultural heritage. These elements serve as carriers of cultural memory, preserve multicultural values, and act as a "line of defense" in maintaining cultural identity on a global scale.